Earnings Management di Indonesia: Studi Empiris pada Periode Sebelum dan Setelah Terlaksananya Program Tax Amnesty - Wibowo, Raden Arief (IAIN Surakarta, 2019)
This study aims to examine earnings management practice in the Indonesian companies, before, during, and after the tax amnesty program, and compare it through testing the difference in the absolute value of discretionary accruals before, during, and after the tax amnesty program. To conduct this analysis, this study uses 42 samples of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2018. Data from all company samples are arranged in the form of Discretionary Accruals, Non-Discretionary Accruals, and Absolute Discretionary Accruals. The results indicate that there are earnings management practices before the tax amnesty program, and it is greater during the tax amnesty, and smaller after the tax amnesty. Based on the results of different tests, this study also shows that there are differences in the value of Absolute Discretionary Accruals in the tax amnesty program (AbsPre) and Absolute Discretionary Accruals after the tax amnesty program (AbsPost), so the hypothesis states that there is difference between earnings management before the tax amnesty program and after the tax amnesty program, can be accepted. In addition, the amount of Absolute Discretionary Accruals before the tax amnesty program (AbsPre) which tends to be higher 68.37% or almost 70%, shows that there is a great effort made by the management of the company in order to make the company looks outperformed to the investors. Keywords: Tax Amnesty, Earnings Management JEL Classification: M41, 023, G18, G20, H71